MODERN TRENDS AND PROBLEMS OF EDUCATION SERVICES EXPORT IN THE CONTEXT OF EURASIAN INTEGRATION - I. V. Medynskaya (Дискурс, 2018)
The current stage of the global society evolution shows that it is a priority concern to export educational services for expanding political, economic and cultural relations among the Eurasian Economic Union member countries. The article examines problems and prospects of developing international academic cooperation of higher education organizations in the context of Eurasian integration. It is defined that academic and business integration in the EAEU countries increases the level of the national economies' publicity, creates a single information space, and is responsible for intensifying international technology movement. The need to use information and communication technologies which make it possible for education to satisfy global development trends is shown.